Learning speed is affected by personality and reproductive investment in a songbird (2017)
ABSTRACT: Individuals from different taxa, including songbirds, differ consistently in behaviour and personality when facing different situations. Although our understanding of animal behaviour has increased, knowledge about between-individual differences in cognitive abilities is still limited. By using an experimental approach and a free-living songbird (Parus major) as a model, we attempted to understand between-individual differences in habituation to playbacks (as a proxy of learning speed), by investigating the role of personality, age and reproductive investment (clutch size). Pre-breeding males were tested for exploration (a proxy of personality) in standardized conditions. In addition, the same individuals were exposed to three playbacks in the field during incubation. Birds significantly moved less, stayed further away and overlapped less the playback with successive playback stimulation. While a decrease in the locomotor behaviour can be explained by personality, differences in habituation of overlapping were predicted by both reproductive investment and personality. Fast explorers habituated less. Moreover, males paired to females with larger clutches did not vary the intensity of overlapping. Since habituation requires information for recognition of non-threatening signals, personality may bias information gathering. While fast explorers may collect less information from the environment, slow explorers (reactive birds) seem to pay attention to environmental clues and collect detailed information. We provided evidence that the rate of habituation of behavioural responses, a proxy of cognitive abilities, may be affected by different factors and in a complex way.